Pelatihan Media E-learning Edmodo untuk Optimalisasi Pembelajaran - Ekasatya Aldila Afriansyah; Deddy Sofyan; Nita Puspitasasri; Irena Puji Lurytawati; Rostina Sundayana; Iyam Maryati; Mega Achdisty Noordyan; Basuki Basuki (Jurnal Pekemas, 2020)
The problem of teachers' weakness in using e-learning media to support the learning process is the theme raised in this training. The solution offered from this training is Edmodo e-learning media. The purpose of this training activity was to introduce Edmodo to the e-learning media for teachers in Garut. The research implementation method consists of five stages, namely: introduction, socialization, training, practice, and monitoring. The object of this training activity is alumni teachers from the Garut Indonesian Institute of Education campus. The training was conducted in two sessions, namely: presentation of material and practice. The usefulness of the training in the use of Edmodo e-learning media is evident from the commitment of the training participants about the plan to implement Edmodo's e-learning media in their learning class. The results of the evaluation of the implementation of this training indicate that this training is useful to support the teaching and learning process carried out in schools. The training method can improve the skills of teachers in using Edmodo e-learning media, both as teachers, students, and parents of students. The conclusion of this training is the knowledge in the use of Edmodo e-learning media for teachers so that it is hoped that in the future teachers in Garut will use Edmodo e-learning media in supporting teaching and learning activities